Enxertia no desenvolvimento e qualidade de frutos de tomateiro sob diferentes porta-enxertos em cultivo protegido - Sirtoli, Luchele Furlan; Cerqueira, Reginaldo Conceição; Rodrigues, João Domingos [UNESP]; Goto, Rumy [UNESP]; Braga, Camila de Lima [UNESP] (My University, 2011)
The aim of this work was to evaluate the development of plants and the physical-chemical characterization of fruits of tomato hybrid Platinum, grafted and ungrafted. The design was completely randomized design with eight treatments, three replications and five plants per plot, seven rootstocks, R601, R602, R603, Guardian, Protective, Spirit and Magnet, grafted on hybrid Platinum and their respective ungrafted plants. Evaluations were made of incompatibility of plants, production and physicalchemical properties of fruits. The highest percentage of surviving plants occurred for hybrids Magnet and R603, being more efficient in controlling bacterial wilt. There were no incompatibility of plants and differences for the variables water loss, texture, SS, AT, SS / AT (ratio) as well as productivity. To note the pH differences were significant, and the rootstock Protetor, Magnet and Guardião with the ungrafted plants had lower pH, while the rootstock R601 showed higher pH of the fruit. The combination of rootstock R603 Platinum with the commercial hybrid showed resistance to Ralstonia solanacearum, besides the tendency to increase the productivity of plants.

O presente trabalho objetivou avaliar o desenvolvimento de plantas e a caracterização físico-química de frutos de tomateiro híbrido Platinum, enxertadas e pé-franco. O delineamento adotado foi inteiramente casualizado com oito tratamentos, três repetições e cinco plantas por parcela, sendo sete porta-enxertos, R601, R602, R603, Guardião, Protetor, Spirit e Magnet, enxertados no híbrido Platinum e o seu respectivo pé-franco. Foram feitas avaliações de incompatibilidade de plantas, produção e caracterização físico-químicas dos frutos. A maior porcentagem de plantas sobreviventes ocorreu para os híbridos R603 e Magnet, sendo mais eficientes para o controle de murcha bacteriana. Não foram observadas incompatibilidade entre enxerto e porta-enxerto e diferenças para as variáveis perda de água, textura, SS, AT, relação SS/AT (ratio) bem como produtividade. Para o pH dos frutos os menores valores foram observados para os portaenxertos Protetor, Magnet e Guardião juntamente com o pé-franco. A combinação do porta-enxerto R603 com o híbrido comercial Platinum mostrou-se resistente a Ralstonia solanacearum, além da tendência de aumento na produtividade de plantas.
Grafting in the development and fruit quality of tomato under different rootstocks in protected cultivation
Keywords: Fruit flavor; Incompatibility; Lycopersicon esculentum Mill; Resistance; Incompatibilidade; Lycopersicon esculentum Mill; Resistência; Sabor de frutos